Exergy and exergoeconomic assessment of sustainable light olefins production from an integrated methanol synthesis and methanol-to-olefins system. (1st May 2022) - Detchusananard, Thanaphorn; Prasertcharoensuk, Phuet; Patcharavorachot, Yaneeporn; Maréchal, François; Arpornwichanop, Amornchai
Abstract: Integrated methanol synthesis and methanol-to-olefins systems are considered attractive and promising technologies to produce light olefins from syngas derived from biomass feedstock. In this study, a flowsheet model of a proposed system was developed and employed for system design and analysis. The system consists of four main parts: methanol synthesis, methanol-to-olefins process, olefins separation, and power plant. The effects of important operating parameters on the exergy efficiency were investigated to determine the optimal operating conditions to achieve the maximum exergy efficiency of this system. The results indicate that the methanol synthesis process should be operated at temperature, pressure, and recycling ratio of 250 °C, 150 bar, and 0.85, respectively, whereas the methanol-to-olefins process should be operated at a temperature of 480 °C and the power plant should be run at steam temperature and steam pressure of 650 °C and 50 bar, respectively. Heat integration based on a pinch analysis was subsequently performed to improve the system energy usage, resulting in a 9.29% increase in the exergy efficiency of the integrated system. An exergoeconomic analysis of the integrated system with the designed heat exchanger network was performed. The results show that the power plant has the highest cost rate of exergy destruction and total cost rate. Moreover, the syngas feedstock cost has the greatest impact on the exergoeconomic indicators; it is necessary to minimize this cost to achieve economic viability of the process for industrial use. The production of light olefins from the integrated methanol synthesis and methanol-to-olefins system using a renewable syngas feedstock has a potential to reduce greenhouse gas emissions due to the use of renewable sources replacing fossil sources. Highlights: Sustainable olefins production was proposed via an integrated methanol synthesis and methanol-to-olefins system. Exergy analysis was carried out to select optimal operating conditions. The maximum exergy efficiency of the system is 59%. Key economic parameters were investigated by performing exergoeconomic analysis. Power plant has the highest cost rate and syngas cost affects the economic indicators.